Stress in Chachapoyas Quechua: a Linguistic Stratum of the Chacha Language or a Proto-Quechua Vestige - Valqui, Jairo (2018)
This article presents preliminary data of the research project on the Stress Patterns found in Chachapoyas Quechua and its Implications for the Reconstruction of Protoquechua. This is the thesis project for a PhD degree in Linguistics at the National University of San Marcos. The state of the art around the accent in protoquechua has not offered so far a proposal on how their accent patterns would have been like (Cf. Torero, 1964, Parker, 2013, Cerrón-Palomino, 2003). The hy- pothesis of our project is that the accentual patterns of Chachapoyas Quechua maintains its prosodic aspect from the protoquechua and not from the Chacha language studied by Taylor (2000) and Valqui & Zie-mendorff (2016). In this article, unpublished data of acoustic charac- teristics of this variety that were collected in towns of the provinces of Chachapoyas and Luya in the department of Amazonas are presented. In addition, these data are discussed, mainly, with the accentual pat- terns of Ferreñafe Quechua described by Escribens (1977) and those of Huancapón Quechua described by Pineda (1994).